Środowisko przyrodnicze i zagospodarowanie form eolicznych w gminie Szadek - Kobojek, Elżbieta; Kobojek, Sławomir (Biuletyn Szadkowski, 2013)
Sand hills, dunes and sand sheets are eolian landforms, on which specific sensitive ecosystems develop. They are characteristic feature of many areas situated in central Poland. Sandy areas with dunes are also found in the commune of Szadek. Wind-deposited sand bodies have accumulated on moraine plains, outwashes and floodplain terraces in the valleys of the Pichna and Brodnia rivers. Eolian formations have various shapes, with predominance of parabolic dunes, ridges and sand hills. They are built offine-grained and coarser sands 1-10 meters thick. Quartz dominates in their mineral composition. Sand-deposits are characterized by high permeability, which is why they produce dry ecosystems. Arid sands are covered by low-class pod sols, easily eroded by wind. For that reason this type of ecosystems should remain afforested, as the cutting down of trees can result in blowing away the soil and eventually destruction of the entire formation. Such situations are known to have happened in the past. In the commune of Szadek, the majority of the dunes are overgrown with forest, which is the most advantageous solution.